1970
DOI: 10.1115/1.3424954
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Lateral Skewing in a Three-Dimensional Turbulent Boundary-Layer Flow

Abstract: The results of an experimental program are reported on, wherein the lateral flow in a low-speed, three-dimensional, turbulent, incompressible boundary layer inside a recurving duct was made to reverse itself completely. In such a reversal process there occurs a region of flow where the boundary layer experiences lateral flow in two different lateral directions simultaneously. The physical arguments which support the existence of such flow regions with simultaneous lateral skewing are discussed and supported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1972
1972
1999
1999

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Eichelbrenner (1963) and Eichelbrenner & Peube (1966) were the first to draw attention to cross-over profiles. Klinksiek & Pierce (1970) measured mean velocity profiles with two-sided lateral skewing in an 'S'-shaped channel of rectangular crosssection and Webster, DeGraaff & Eaton (1996) in a boundary layer over a swept bump. Recent measurements were performed by Schwarz & Bradshaw (1992, 1994 and by Compton & Eaton (1995) in a curved duct with unilaterally skewed velocity profiles and byÖlçmen & Simpson (1995b), in the flow of a wing-body junction.…”
Section: Introductionmentioning
confidence: 99%
“…Eichelbrenner (1963) and Eichelbrenner & Peube (1966) were the first to draw attention to cross-over profiles. Klinksiek & Pierce (1970) measured mean velocity profiles with two-sided lateral skewing in an 'S'-shaped channel of rectangular crosssection and Webster, DeGraaff & Eaton (1996) in a boundary layer over a swept bump. Recent measurements were performed by Schwarz & Bradshaw (1992, 1994 and by Compton & Eaton (1995) in a curved duct with unilaterally skewed velocity profiles and byÖlçmen & Simpson (1995b), in the flow of a wing-body junction.…”
Section: Introductionmentioning
confidence: 99%
“…The question of a collateral near-wall region of flow in threedimensional turbulent layers is still open. The work of Francis and Pierce [36], 4 Klinksiek and Pierce [37], Gardow [38], Johnston [39], Hornung and Joubert [40], M. Smith [41], P. D. Smith [42], Lewkowicz [43], and Prahlad [44], all show from two up to seven experimentally determined points which suggest a collateral near-wall region of flow when w/U is plotted against u/U in a velocity polar (or hodograph) figure. In all cases the velocity polars referred to above were characterized by lateral flow in only one direction so that these polars can be put into a single class of flows.…”
mentioning
confidence: 99%
“…In closing, it is suggested that the question of defining a limiting wall streamline in a three-dimensional turbulent boundary la3 r er flow must be approached with caution, since the existence of a collateral near-wall region of flow is open. The experimental work of Francis and Pierce [9], e Klinksiek and Pierce [10], Gardow [11], Johnston [12], Hornung and Joubert [13], M. Smith [14], P. D. Smith [15], Lewkowicz [16], Prahlad [17] 6 Numbers in brackets designate Additional References at end of Discussion.…”
mentioning
confidence: 99%